Selective hydrogenation of fatty acids and methyl esters of fatty acids to obtain fatty alcohols-a review - Sánchez, María Amparo (2017)
In this paper, a review of the evolution of different catalytic systems and operating conditions used in the selective hydrogenation of acids and esters of fatty acids to obtain fatty alcohols, which have broad industrial applications in the oleochemical industry, is presented. In addition, the current status of the different technologies used industrially (Lurgi, Davy and Henkel) for obtaining fatty alcohols, as well as major global sources of raw materials for the oleochemical industry are put forward. Finally, the reaction mechanisms of the selective hydrogenation process of oleic acid and methyl oleate to obtain the corresponding unsaturated alcohol as well as the new catalysts proposed by researchers are described.